EUniversal: the universal market enabling interface as a way to unlock flexibility solutions for cost-effective management of smarter distribution grids - Simão, Tiago; Terras, José M.; Gouveia Aguiar, Clara; Gerard, Helena; Meeus, Leonardo; Calpe, Carmen; Noske, Slawomir; Otuszewski, Thomas; Cossent Arín, Rafael; González, Florian (My University, 2025)
This paper offers an overview of EUniversal H2020 project which aims to develop and demonstrate a replicable solution for the interaction of the DSO (through the UMEI – Universal Market Enabling Interface) with the new flexibility markets and services specified and developed within the project. The UMEI brings forward a universal, open, adaptable and modular approach to interlink active system management with electricity markets and foster the provision of flexibility services, also acknowledging the activation needs of DSOs and the coordination requirements with other commercial parties and TSOs. EUniversal comprises 3 demonstration sites: Portugal, focusing on the demonstration of the UMEI concept and of new data driven network operation tools for the management of market driven flexibility services for LV and MV grids; Germany, addressing congestion management using market-driven flexibility via the UMEI in LV networks; Poland, focusing on grid observability and future networks supporting flexibility management via the UMEI. The interdisciplinary and complementary expertise of the project partners will allow to capture and cover different requirements and solutions and to maximise their impact and replicability across Europe. Lastly, the project will develop business models archetypes for flexibility mechanisms, perform a Cost Benefit Analysis and deliver a Roadmap.